Environmental pollution, hydropower energy consumption and economic growth: Evidence from G7 countries - Bildirici, Melike E.; Gokmenoglu, Seyit M. (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The aim of this study is to examine the relationship among environmental pollution, economic growth and hydropower energy consumption in the different regimes of the business cycles for G7 countries over the period of 1961-2013. We used Markov Switching-Vector Autoregressive (MS-VAR) and MS-Granger Causality methods to achieve this goal since the traditional methods examine the causality by assuming all period in the same level. Unlike traditional methods, these methods allow for determining the relationship and casual dynamics between variables in different regimes. The causality results obtained for different regimes assisted to suggest policy recommendations for each regime individually. According to analysis results, it was found that there is bidirectional Granger causality between carbon dioxide emissions and economic growth in the crisis regime and in the high growth regime while carbon dioxide emissions are Granger cause of economic growth in all regimes in general. We found evidence that hydropower energy consumption is Granger cause of economic growth in general whereas there is a bidirectional causality for some G7 countries. Furthermore, the results from these models indicate that in the first, second and third regimes, carbon dioxide emissions are Granger cause of hydropower energy consumption and hydropower energy consumption is Granger cause of carbon dioxide emissions for some G7 countries.
Keywords: Economic Growth; Hydropower Energy Consumption; Carbon Dioxide Emissions; MS-VAR; MS-Granger Causality; RENEWABLE ENERGY; CO2 EMISSIONS; HYDROELECTRICITY CONSUMPTION; ELECTRICITY CONSUMPTION; CAUSAL RELATIONSHIP; EMPIRICAL-EVIDENCE; STRUCTURAL-CHANGE; TIME-SERIES; NEXUS; GDP; Science & Technology - Other Topics; Energy & Fuels